A ROS-based simulation and control framework for in-orbit multi-arm robot assembly operations - Bhadani, Saksham; Dillikar, Sairaj R.; Pradhan, Omkar N.; Cotrina de los Mozos, Irene; Felicetti, Leonard; Upadhyay, Saurabh; Tang, Gilbert (European Space Agency (ESA), 2023)
This paper develops a simulation and control framework for a multi-arm robot performing in-orbit assembly. The framework considers the robot locomotion on the assembled structure, the assembly planning, and multi-arm control. An inchworm motion is mimicked using a sequential docking approach to achieve locomotion. An RRT* based approach is implemented to complete the sequential assembly as well as the locomotion of MARIO across the structure. A semi-centralised controller model is used to control the robotic arms for these operations. The architecture uses MoveIt! libraries, Gazebo simulator and Python to simulate the desired locomotion and assembly tasks. The simulation results validate the viability of the developed framework.
Keywords: Robot Operating System (ROS); On-orbit Assembly; Locomotion; Free-Floating nature; Multi- Manipulator System; Multi-Armed Robot for In-Orbit Operations; Spatial Reticular Structure (SRS); Modular Truss Structure; Path planning